A FEASIBILITY STUDY ON ORTHOGONAL SAW TAG DESIGN UTILIZING A NOVEL TIME-FREQUENCY LATTICE APPROACH - SURESH, KASYAP (2021)
Fast and error-free identification of items are the primary objectives for many large scale industrial logistics applications such as in big warehouses, store rooms, factories, and industries.